THE EFFECT OF Chlorella sp FLOUR FORTIFICATION ON THE QUALITY OF DODOL ADDED WITH SEAWEED (Eucheuma cottoni) - Miranda, Angger; Sari, N Ira; ', Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study aimed to determine the effect of Chlorella sp flour fortification on the quality of dodol added with seaweed (Eucheuma cottoni) with organoleptic, and chemical. The method used was an experimental method and design as completely randomized design (CRD). The treatment fortification flavour Chlorella sp with consist four taraf, the taraf is (C1) Chlorella sp without flavour, (C2) 2 gram Chlorella sp fortification flavour, (C3) 4 gram Chlorella sp fortification flavour, (C4) 6 gram Chlorella sp fortification flavour. The parameter test of the reseach is organolephtic and chemical.The result of the reseach is 2 gram Chlorella sp fortification flavour showed the best of the treatment, with the characteristic is shiny, green and tidy (7.91), aroma typical of dodol and slightly smelly Chlorella sp (7.99), flavor sweet and a little taste of Chlorella sp (7.96), chewy textures and not sticky chewed (8.28). It contained of water 3.60%, protein 28.52%, fat 21,60% and crude fiber 1,32%.Keywords: Eucheuma cottoni, Chlorella sp, dodol.